INHIBITION EFFECT OF SOME COMMERCIAL CORROSION INHIBITORS ON MILD STEEL IN 7.0 M PHOSPHORIC ACID - CHELARU, Julieta Daniela; CIOBRA, Mihaela; MUREȘAN, Liana Maria (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Corrosion tests were carried out in order to find the best inhibitor for the protection of steel pipelines used in H3PO4 and fertilizers industry. The corrosion inhibition efficiency of five commercial inhibitors was investigated on mild steel by using electrochemical methods (EIS and polarization curves) in a 7M H3PO4 solution (pH 0.5). The efficiency of best corrosion inhibitors was tested at different concentrations.